Different N-Glycosylation Sites Reduce the Activity of Recombinant DSPAα2 - Peng, Huakang; Wang, Mengqi; Wang, Nan; Yang, Caifeng; Guo, Wenfang; Li, Gangqiang; Huang, Sumei; Wei, Di; Liu, Dehu (Current Issues in Molecular Biology, 2022)
Bat plasminogen activators α2 (DSPAα2) has extremely high medicinal value as a powerful natural thrombolytic protein. However, wild-type DSPAα2 has two N-glycosylation sites (N185 and N398) and its non-human classes of high-mannose-type N-glycans may cause immune responses in vivo. By mutating the N-glycosylation sites, we aimed to study the effect of its N-glycan chain on plasminogen activation, fibrin sensitivity, and to observe the physicochemical properties of DSPAα2. A logical structure design was performed in this study. Four single mutants and one double mutant were constructed and expressed in Pichia pastoris. When the N398 site was eliminated, the plasminogen activator in the mutants had their activities reduced to ~40%. When the N185 site was inactivated, there was a weak decrease in the plasminogen activation of its mutant, while the fibrin sensitivity significantly decreased by ~10-fold. Neither N-glycosylation nor deglycosylation mutations changed the pH resistance or heat resistance of DSPAα2. This study confirms that N-glycosylation affects the biochemical function of DSPAα2, which provides a reference for subsequent applications of DSPAα2.